2018
DOI: 10.26656/fr.2017.2(3).275
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of protein content and effect on technological properties of wheat bread with the addition by cobia (Rachycentron canadum)

Abstract: The aim of this work was to improve the protein content of the wheat bread and to study the technological properties, incorporating Cobia (Rachycentron canadum) minced proteins (CMP). The influence of CMP on the characteristics of wheat bread, such as texture, color, specific volume (SV), protein and lipids content were evaluated. Wheat flour was replaced by CMP at different levels of substitution, and hydrogenated vegetable fat was added in different levels according to 2 2 central composite rotational design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
4
12
0
1
Order By: Relevance
“…e gross composition of the bread samples was mainly dependent on the constituents of the skim milk, egg shell, and oyster shell. e obtained results were consistent with the results for bread enriched with moringa seed flour and bread produced from blends of maize, wheat, and orange-fleshed sweet potato flour documented by Bibiana et al [21] and Fagundes et al [22]. e obtained results were consistent with the results of Odunlade et al [23], who reported increased levels of protein (9.50 to 13.93%), fibre (1.81 to 4.00%), and ash (1.05 to 2.38%) when vegetable powders were added to wheat bread during preparation of dough.…”
Section: Discussionsupporting
confidence: 91%
“…e gross composition of the bread samples was mainly dependent on the constituents of the skim milk, egg shell, and oyster shell. e obtained results were consistent with the results for bread enriched with moringa seed flour and bread produced from blends of maize, wheat, and orange-fleshed sweet potato flour documented by Bibiana et al [21] and Fagundes et al [22]. e obtained results were consistent with the results of Odunlade et al [23], who reported increased levels of protein (9.50 to 13.93%), fibre (1.81 to 4.00%), and ash (1.05 to 2.38%) when vegetable powders were added to wheat bread during preparation of dough.…”
Section: Discussionsupporting
confidence: 91%
“…Samples with added SFP exhibited lower moisture contents as compared to the control breads. Previous research has shown similar results when cobia powder, flaxseed, and lupin have been added to breads [5,13]. The energy value obtained in SFP-enriched breads was higher ( p < 0.05) than the control bread and this may be related to the higher lipid content of the breads.…”
Section: Resultssupporting
confidence: 62%
“…Food rich in polyphenols have the potential to protect against various diseases associated with oxidative damage, such as cancer, and cardiovascular and neurological disease [11]. In recent years, to achieve this, many nutritional ingredients such as carob [12], flaxseed and lupin [5], mushroom powder [6], cobia [13], and Chlorella vulgaris [8] have been incorporated into bread to improve its nutritional composition and product quality. Other products, such as pasta [14] and pizza [15], have been developed with the inclusion of fish powder in their formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Fagundes et al . () also reported the addition of cobia (fish) protein, which contains high levels of essential amino acids, increases the crumb firmness of wheat bread. The texture of wheat bread is negatively affected by adding proteins in the formula due to the alternation of gluten network.…”
Section: Resultsmentioning
confidence: 96%